Quantum wave packet study of O(1D)+HCl(v)?ClO(v?)+H reaction - Bulut, N; Yildiz, A; Gögtas, F; Akpinar, S (John Wiley & Sons Inc, 1999)
We have performed quantum wave packet calculations of vibrational reaction probabilities for two-dimensional O(D-1) + HCl(v) --> ClO(v') + H reaction. The time-dependent quantum method described here allows one to compute the reaction probabilities over a broad range of collision energy from a single solution of the time-dependent Schrodinger equation. (C) 1999 John Wiley & Sons, Inc.
Keywords: reaction dynamics; reactive scattering; reaction probabilities; wave packet study